Vocal cord immobility after lateral pharyngotomy extraction of the impacted dentures in the upper esophagus: A Case Report - Tamin, Susyana; Koento, Trimartani; Hutauruk, Syahrial Marsinta; Supit, Ivana; Ardiantara, Sabda (TALENTA, 2024)
Impaction of foreign bodies in the esophagus is a frequent emergency in otorhinolaryngology. However, diagnosing and managing denture impaction in the esophagus presents greater challenges compared to other foreign bodies, often leading to various complications. This study reported a rare case of vocal cord immobility after the evacuation of denture impaction in the esophagus using lateral pharyngotomy. The patient, a 73-year-old man, experienced throat discomfort after swallowing a denture an hour before admission. According to the CT scan carried out, a 3.7 cm long denture was found around the T3-T5 spine level and was located 3 mm lateral right to the descendant aorta and 4 mm posterior of the trachea. During esophagoscopy extraction, the denture was stuck in the upper esophagus and was successfully evacuated by lateral pharyngotomy. Subsequently, the patient developed vocal cord immobility, and this case underscores the importance of considering vocal cord complications following the extraction of a denture impaction in the esophagus.